2005
DOI: 10.1016/j.agwat.2004.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Regulated deficit irrigation during the kernel-filling period and optimal irrigation rates in almond

Abstract: The use of Regulated deficit irrigation (RDI) in almond, applied during the kernel-filling phase, was evaluated over four consecutive years. To determine the reference optimal irrigation rate, three treatments were applied: T-100, which was irrigated by replacing crop evapotranspiration; T-130, which was irrigated by applying 30% more water than in T-100 and T-70, which received 30% less water than T-100. The RDI treatment received the same irrigation rate as T-100, but during the kernelfilling period irrigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
2
14

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(76 citation statements)
references
References 20 publications
7
53
2
14
Order By: Relevance
“…However, the use of RDI follows the studies carried out by the group at IRTA (Lleida) related with the sensitivity of almond to water deficit as a function of the phenological stage (Girona et al, 1997). Subsequent studies by the same group (Girona et al, 2005a) and others such as those at IMIDA, Murcia and UPCT, Cartagena, Murcia (Nortes, 2008;Egea et al, 2009Egea et al, , 2010 have confirmed almond as a crop ideal for applying RDI strategies.…”
Section: Prunus Spmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of RDI follows the studies carried out by the group at IRTA (Lleida) related with the sensitivity of almond to water deficit as a function of the phenological stage (Girona et al, 1997). Subsequent studies by the same group (Girona et al, 2005a) and others such as those at IMIDA, Murcia and UPCT, Cartagena, Murcia (Nortes, 2008;Egea et al, 2009Egea et al, , 2010 have confirmed almond as a crop ideal for applying RDI strategies.…”
Section: Prunus Spmentioning
confidence: 99%
“…The use of RDI in almond, applied during the kernelf illing phase, was evaluated over four consecutive years by Girona et al (2005a). Average fruit yields recorded were relatively high in all the assayed treatments (kernel yield > 1,400 kg ha -1 ).…”
Section: Prunus Spmentioning
confidence: 99%
“…The negative effects in those studies were not extreme, and the yield reductions were generally associated more strongly with water deficits imposed during postharvest than during hull split. In a 4-year study by Girona et al (2005), a statistically significant (20%) reduction in overall yield was associated with a 40% reduction in water application and a nonsignificant (3%) reduction in kernel dry mass. In our study, the overall treatment difference in kernel dry mass of 2.5% was Weeks from full bloom the study did not measure any almond yield reductions attributable to regulated deficit irrigation.…”
Section: Deficit Irrigation In Practicementioning
confidence: 99%
“…The success of RDI strongly depends on the appropriate use of microirrigation techniques, which allows the control of soil water content (Dichio et al, 2007). RDI has been used successfully maintaining yield and fruit quality in many fruit species (Ebel et al, 1995;Girona et al, 2003;Buendía et al, 2008;López et al, 2008), nut species Goldhamer and Beede, 2004;Romero et al, 2004;Girona et al, 2005) citrus species (Sánchez-Blanco et al, 1989;Castel and Buj, 1990;Domingo et al, 1996;Castel, 1999, 2000;Goldhamer and Salinas, 2000), wine grapes (Bravdo and Naor, 1996;McCarthy et al, 2002) and olives (Moriana et al, 2003). The most important research studies related to the application of RDI strategies in apricot trees has been done by RuizSanchez et al (1999RuizSanchez et al ( , 2000bRuizSanchez et al ( , 2004RuizSanchez et al ( , 2007, and Pérez-Pastor et al (2004).…”
Section: Introductionmentioning
confidence: 99%